Single‐dose pharmacokinetic studies of abiraterone acetate in men with hepatic or renal impairment. (17th January 2014) - Marbury, Thomas; Lawitz, Eric; Stonerock, Robert; Gonzalez, Martha; Jiao, James; Breeding, Jim; Haqq, Christopher; Verboven, Peter; Stieltjes, Hans; Yu, Margaret; Molina, Arturo; Acharya, Milin; et al.
Abstract Three open‐label, single‐dose studies investigated the impact of hepatic or renal impairment on abiraterone acetate pharmacokinetics and safety/tolerability in non‐cancer patients. Patients (n = 8 each group) with mild/moderate hepatic impairment or end‐stage renal disease (ESRD), and age‐, BMI‐matched healthy controls received a single oral 1, 000 mg abiraterone acetate (tablet dose); while patients (n = 8 each) with severe hepatic impairment and matched healthy controls received 125‐ and 2, 000‐mg abiraterone acetate (suspension doses), respectively (systemic exposure of abiraterone acetate suspension is approximately half to that of tablet formulation). Blood was sampled at specified timepoints up to 72 or 96 hours postdose to measure plasma abiraterone concentrations. Abiraterone exposure was comparable between healthy controls and patients with mild hepatic impairment or ESRD, but increased by 4‐fold in patients with moderate hepatic impairment. Despite a 16‐fold reduction in dose, abiraterone exposure in patients with severe hepatic impairment was about 22% and 44% of the Cmax and AUC∞ of healthy controls, respectively. These results suggest that abiraterone pharmacokinetics were not changed markedly in patients with ESRD or mild hepatic impairment. However, the capacity to eliminate abiraterone was substantially compromised in patients with moderate or severe hepatic impairment. A single‐dose administration of abiraterone acetate was well‐tolerated.